Drawing digital : the complete guide for learning to draw & paint on your iPad - Bardot, Lisa (Walter Foster, 2023)
"In Drawing Digital, artist and teacher Lisa Bardot, the expert behind @bardotbrush, introduces the art of digital drawing. Using your tablet and Procreate, or another favorite drawing app, you can leave behind your pencil and paper and make art anywhere and at any time." --